Fuzzy Semi Pre Homeomorphism in Fuzzy Topological Spaces - Y. Majeed, Saleem (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The aim of this paper is to introduce and study new class of fuzzy function called fuzzy semi pre homeomorphism in a fuzzy topological space by utilizing fuzzy semi pre-open sets. Therefore, some of their characterization has been proved; In addition to that we define, study and develop corresponding to new class of fuzzy semi pre homeomorphism in fuzzy topological spaces using this new class of functions.